Incidence of Seasonal Diarrhea among Children at Child's Central Hospital - Abu- Ragheef, layla; Hussein, Abdul-Kadir (Iraqi National Journal of Nursing Specialties, 2007)
Objective: Diarrhea is a symptom of a variety of conditions may attack the child. It considered one ofmam causes of mortality rates especially in low socio- economic level countries. The child can beeasily got dehydration and pass from loss of too much body fluid and due to the Common thoueht ofincreasing the incidence of diarrhea during summer season, this study is done to find out the relationbetween the high incidences rate of diarrhea and weather variationMethodology: This survey conducted in AL- Markazi Child's Teaching Hospital for the year 2005 thedata were gathered from hospital records for the period (January - December) and age groupstaxonomy used by hospital applied. Descriptive statistical analysis and diagrams usedResults: The analysis revealed that the incidence of diarrhea happens all around the year and for thewhole age groups. Summer results pointed out high ratio in relation to the results of spring winter andautumn seasons. Also more incidence seen among the age group (